THE NEUROLINGUISTIC FOUNDATIONS OF LANGUAGE: A THEORETICAL REVIEW OF BROCA’S AREA AND WERNICKE’S AREA IN PSYCHOLINGUISTIC FUNCTIONING (Yavana Bhasha : Journal of English Language Education, 2026)
This article examines the neurocognitive mechanisms of language by exploring the distinct yet interconnected roles of Broca’s area and Wernicke’s area within the human brain. It focuses on how these two regions contribute to language production and comprehension, respectively, and how their interaction forms the core of psycholinguistic processing. The aim of this study is to provide a comprehensive theoretical analysis of the anatomical positioning, functional specialization, and neurological disorders associated with each area. This research is conducted using a qualitative-descriptive method, drawing from classical case studies and contemporary findings in neuroimaging. The discussion integrates insights from historical observations by Paul Broca and Carl Wernicke, and expands to include recent functional MRI and EEG research that demonstrate a more dynamic and interconnected model of language processing. The arcuate fasciculus is discussed as the primary pathway linking Broca’s and Wernicke’s areas, facilitating the reciprocal flow of linguistic information between comprehension and expression. Findings show that both regions are not isolated in function but cooperate within a distributed network, challenging the traditional dichotomy of language centers. It is concluded that understanding the synergy between these areas is essential for explaining the neural basis of language and for advancing clinical approaches in the diagnosis and rehabilitation of aphasia. This theoretical study offers a refined understanding of how specific cortical regions underpin the human capacity for language.